ORTHOFEST KYIV 2025: Інноваційні підходи до лікування поліструктурної травми кінцівок - Board, Editorial (TERRA ORTHOPAEDICA, 2025)
ORTHOFEST KYIV 2025: Інноваційні підходи до лікування поліструктурної травми кінцівок